Ministry of Hamdy Al-Bachachy (the first) 3rd of Jun - 28 Aug. 1944 in Iraq The Ministry forum and the political and economical issues - قحطان حميد كاظم (College of Education for Women, 2019)
This study Studied Ministry of Hamdy Al-Buchachy(the first)and explain the features of this Ministry in a critical time in the history of Iraq. The second world war had began and its end had reached .The political situation in Iraq is so complicated. The Ministry had made many things. The Ministry had situated in internal and external complicated time. The situation in Iraq was so difficult, therefore the recommendor (Abdul-Ilah)asked Hamdy Al- Bachachy to make be the head of the new governments Al-Bachachy had made irrelevant government, thus it didn't last more than three months and the British governorate and of direct in terference in Iraq who worked to reduce the Iraqi army and the Minister of Defence refused that because of the troubles in the north of Iraq(Barzan movement).It worleedhord to improve the internal product and find solutions to the problems of the Iraqi people. In the external issue the Ministry participated in some of the conferences and international meetings that related to economy and finance and making diplomatic relationships with the social countries .as well as the other countries. It worked to develop the ability of governorate istituties especially in management and worker and increasing the number of employers in the Ministries that home a direct relationship with the life of citizens. Thus some of the critics against their Ministry is that it limited the general freedom and democratic freedom so it didn't give the freedom to political parties and the press that represent her.